Some Psychological and Sociological Aspects of a New Mining Town. Implications for Planning (The Australasian Institute of Mining and Metallurgy, 1973)
Studies of human relations are being made by a team of psychologists within management and in the community of Kambalda as a whole. Some of the first results are discussed with reference to extensions required in management when it also has to run a mining town. Implications are noted for town planning policies of the attitudes and preferences of the population with regard to housing and to other major planning areas. Some of the theoretical and practical difficulties of 'planning the human ecology' are outlined.